1996
DOI: 10.2134/jeq1996.00472425002500050020x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Land‐Applied Tertiary‐Treated Effluent on Soil Biochemical Properties

Abstract: Land application is increasingly used for the disposal and treatment of effluents. We investigated how irrigation of tertiary‐treated domestic effluent influenced 14 soil biochemical properties in a Monterey pine (Pinus radiata D. Don) forest on volcanic soils. The soils were irrigated with either effluent or water at two loading rates (49 and 74 mm wk−1). Surface soils (0–5 cm) were collected from the effluent‐irrigated and adjacent nonirrigated control sites annually for 3 yr and for 2 yr from the water‐irri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
18

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 0 publications
3
31
2
18
Order By: Relevance
“…The volatilization of NH 3 -N in acid soils irrigated with the alkaline effluent was a well-known fact (Smith et al, 1996) and might have also occurred in this study. Denitrification processes have been found to be dependent on the effluent organic C concentration (Bouwer and Chaney, 1974;Schipper et al, 1996), the available C in soil (Feigin et al, 1991) and, the irrigation effect on soil resulting in decrease of O 2 (Polglase et al, 1995). In this context, a two fold (Schipper et al, 1996) to fifty fold increases (Friedel et al, 2000) of denitrification rates in TSE irrigated soils have been reported.…”
Section: Mineral Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatilization of NH 3 -N in acid soils irrigated with the alkaline effluent was a well-known fact (Smith et al, 1996) and might have also occurred in this study. Denitrification processes have been found to be dependent on the effluent organic C concentration (Bouwer and Chaney, 1974;Schipper et al, 1996), the available C in soil (Feigin et al, 1991) and, the irrigation effect on soil resulting in decrease of O 2 (Polglase et al, 1995). In this context, a two fold (Schipper et al, 1996) to fifty fold increases (Friedel et al, 2000) of denitrification rates in TSE irrigated soils have been reported.…”
Section: Mineral Nitrogenmentioning
confidence: 99%
“…Denitrification processes have been found to be dependent on the effluent organic C concentration (Bouwer and Chaney, 1974;Schipper et al, 1996), the available C in soil (Feigin et al, 1991) and, the irrigation effect on soil resulting in decrease of O 2 (Polglase et al, 1995). In this context, a two fold (Schipper et al, 1996) to fifty fold increases (Friedel et al, 2000) of denitrification rates in TSE irrigated soils have been reported. Also, the microbial N immobilization should be considered because: (i) most of the effluent-N occurred as NH 4 + -N that represented the preferred microbial inorganic-N (Stevenson, 1986); (ii) after STSE application to the soil, TN concentrations increased (Fig.…”
Section: Mineral Nitrogenmentioning
confidence: 99%
“…Such effect may be attributed to the high content of basic cations viz. Na + , Ca 2+ and Mg 2+ in the WW, wh ich after accu mulat ion in surface soil layer for a long period of t ime [51], leads to increase soil pH. The increased in soil pH (Table 3) has been referred e xclusively to the high content of Ca 2+ and Mg 2+ of pharmaceutical effluents applied to the soil [30].…”
Section: Soil Phmentioning
confidence: 99%
“…This method has been used to treat effluent from townships, meatworks, dairy factories, and dairy farms (Schipper et al 1996;Selvarajah 1996;Cameron et al 1997;Tomer et al 1997;Sparling et al 2001). A major concern in New Zealand at present is the potential impact of farm dairy effluent (FDE) on the environment (Environment Waikato 1998;Wellington Regional Council 1999b).…”
Section: Introductionmentioning
confidence: 99%